Variation of spin-orbit torque and spin transport properties by V alloying in β-W-based magnetic heterostructures. (1st April 2022) - Kim, Gyu Won; Lee, Jeong Kyu; Kim, Taehyun; Lee, Min Hyeok; Cha, In Ho; Cho, Jiung; Lee, OukJae; Kim, Young Keun
Abstract: Of transition metals, β-W exhibits the maximum charge-to-spin conversion efficiency. However, due to the lack of phase stability, the β-W-based alloy has rarely been investigated as a spin current generating layer. This study examines W–V alloy layers with various W100-x Vx /CoFeB/MgO/Ta heterostructure compositions. X-ray diffraction confirms that the β-W matrix is conserved up to a V content of 20 at%. We attain a maximum damping-like torque efficiency of −0.45 ± 0.04 for the W80 V20 alloy-based heterostructure through the harmonic response method. Furthermore, we determine the spin diffusion length of the W80 V20 layer and specify the interfacial spin transparency of the W80 V20 /CoFeB structure by adopting the spin diffusion model. Consequently, we suggest an intrinsic spin-Hall angle of −0.86. In addition, we observe in-plane current-induced switching. Our results establish the potential of the β-phase W-V alloy layer as a spin current source layer in spintronic devices. Graphical Abstract: A W-V alloy-based SOT free-layer structure is studied based on the harmonic response of the magnetization. An optimized W-V alloy composition presents substantially improved charge-to-spin conversion efficiency as well as SOT switching efficiency. In addition, for the optimized W-V alloy composition, spin transport related parameters, including the spin diffusion length and spin-Hall conductivity, are investigated. Image, graphical abstract